Development of Digital Phonology Teaching Materials Using Shadowing Techniques for Korean BIPA Learners - Nanda Gultom; Yeti Mulyati; Andoyo Sastromiharjo; Halimah Halimah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to produce digital phonology teaching materials using the shadowing technique to improve the pronunciation skills of basic-level Korean BIPA learners. The research method employed Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques involved needs analysis by interviewing BIPA learners and instructors, then conducting pronunciation tests on Korean BIPA learners to identify pronunciation challenges and specific needs for material development. Based on this analysis, the digital teaching materials were designed and developed, then validated by media experts, material experts, and BIPA practitioners. Data analysis techniques in this research included quantitative and qualitative methods. The result showed that the development of digital phonology teaching materials with shadowing techniques for Korean BIPA learners was effective in improving Indonesian pronunciation skills. The evaluation results showed that this teaching material received a very positive response from teachers and learners, with feasibility test scores of 98% and 94% respectively, as well as expert validation that supported the quality of the teaching material. Thus, this digital teaching material not only meets the expected standards, but also offers concrete solutions to the pronunciation challenges faced by Korean BIPA learners, and is ready to be used to improve the effectiveness of Indonesian pronunciation learning.